Temporal Noise Analysis and Measurements of CMOS Active Pixel Sensor Operating in Time Domain - Campos, Fernando de Souza [UNESP]; Ulson, Jose Alfredo C. [UNESP]; Swart, Jacobus W.; Deen, M. Jamal; Marinov, Oginan; Karam Junior, Dib; IEEE (Ieee, 2013)
Image sensors in standard CMOS technology are increasing used for consumer, industrial and scientific applications due to their low cost, high level of integration and low power consumption. Further, image sensors in mainstream complementary metal-oxide-semiconductor (CMOS) technology are preferred because they are the lowest cost and easiest/fastest option to implement. For CMOS image sensors, a key issue is their noise behavior. Therefore, we have studied the noise characteristics of CMOS image sensors operating in time domain. Two important noise sources are the reset noise and integration noise. The reset noise is due to the reset in CMOS image sensors operating in voltage domain. The integration noise is that accumulated during light integration and was found to be the constant, independent of light intensity. Our circuit analysis shows that the signal-to-noise ratio (SNR) is also constant and independent of light intensity. At low light levels the constant SNR is higher compared to others CMOS image sensors presented in the literature. We have implemented a time domain CMOS image sensor in AMS CMOS 0.35um technology. Our measurements results show that the SNR level is approximately constant to 43dB.
Keywords: active pixel sensor; high dynamic range; low noise; cmos photodetctor